The efficacy and safety of radiotherapy and immunotherapy with or without anlotinib in driver gene-negative advanced non-small cell lung cancer - Miao, Weijian; Sun, Jingjing; Tao, QiMeng; Zhou, Yan; Jiang, Hao (Frontiers in Oncology, 2026)
BackgroundRadiotherapy paired with immune checkpoint inhibitors (ICIs) has benefited patients with driver gene-negative NSCLC, although treatment resistance remains an obstacle. Anlotinib, a broad-spectrum tyrosine kinase inhibitor, has potential to reinforce immunotherapy by modifying the tumor environment. This study investigates whether incorporating anlotinib can amplify the efficacy of combined treatment protocols.MethodsA total of 203 individuals diagnosed with stage IIIB-IV NSCLC were retrospectively assessed. Treatment occurred at the First Affiliated Hospital of Bengbu Medical University between 2021 and 2023. Patients were grouped into those receiving radiotherapy and immunotherapy (n=123) and those receiving anlotinib in addition (n=80). Clinical outcomes assessed included PFS, OS, response metrics, and treatment-related side effects.ResultsOver a median follow-up of 26 months, the group receiving anlotinib showed enhanced median PFS (10.0 months vs 6.0 months, P = 0.043 HR: 0.708, 95% CI: 0.496–1.009). However, there was no statistically significant difference in overall survival (OS) between the two groups (median OS: 20.0 vs. 18.0 months; P = 0.344, HR:0.848 95% CI:0.597-1.205). the RT+IO+A regimen demonstrated a 10% higher ORR than the RT+IO regimen (45.0% vs. 35.0%), while the DCR was similar between the two groups (88.8% vs. 91.1%). Toxic effects were manageable but more frequent in the triple-therapy group.ConclusionThe triple regimen improved disease stabilization but did not yield OS benefits. Due to the increased toxicity associated with the addition of anlotinib, Future research is required to weigh advantages against added toxicity.